THE CORRELATION BETWEEN READING HABITS OF THE THIRD YEAR ENGLISH STUDY PROGRAM STUDENTS OF UNIVERSITAS RIAU AND THEIR WRITING ABILITY - Febriani, Deswinda; Purwanti, Indah Tri; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was aimed to find out the correlation between reading habits of the third year English Study Program Students of Universitas Riau and their writing ability. The sample of this research was one of three classes of the third year students of the English Study Program that were chosen by using cluster random sampling technique. The population of this research was 36 students. There were two variables of data that were collected in this research: reading habits and writing ability. The reading habits data were gained by using a questionnaire and the writing ability data were collected from a writing test. The results revealed that the reading habits of the population was on ‘high’ level and their writing ability is classified as a good level. The results also showed that there is a significant correlation between reading habits and their writing ability. In conclusion, reading habits of students has a significant influence on students’ ability in writing.Key Words: Correlation, Reading Habits, Writing Ability